Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Đặt \(A=\frac{1.2+2.4+3.6+4.8+5.10}{4+6.8+9.12+12.16+15.20}\)
\(\Rightarrow A=\frac{1.\left(1+2\right)+2.\left(1+2\right)+3.\left(1+2\right)+4.\left(1+2\right)+5.\left(1+2\right)}{4+2.\left(3+4\right)+3.\left(3+4\right)+4.\left(3+4\right)+5.\left(3+4\right)}\)
\(\Rightarrow A=\frac{\left(1+2+3+4+5\right).\left(1+2\right)}{4+\left(2+3+4+5\right).\left(3+4\right)}\)
\(\Rightarrow A=\frac{\left(1+5\right).5:2.\left(1+2\right)}{4+\left(2+5\right).4:2.\left(3+4\right)}\)
\(\Rightarrow A=\frac{6.5:2.3}{4+7.4:2.7}=\frac{45}{4+98}=\frac{45}{102}=\frac{15}{34}\)
Vậy \(A=\frac{15}{34}\)
Chúc bn học tốt
1. -x+20 = -(-15)-8+13
=> -x=15-8+13-20
=> -x=0
=> x=0
2. -(-10)+x=-13+(-9)+(-6)
=> 10+x=-13-9-6
=> x = -13-9-6-10
=> x = -38
3. 8-(-12)+10=-(-14)-x
=> 8+12+10=14-x
=> x = 14-8-12-10
=> x = -16
4. -(+12)+(-x)-(-3)=5-(-7)
=> -12-x+3=5+7
=> -x=5+7+12-3
=> -x=21
=> x=-21
5. 14-x+(-10)=-(-9)+(+15)
=> 14-x-10=9+15
=> -x=9+15-14+10
=> -x=20
=> x=-20
6. 12-(-17)+(-3)=-5+x
=> 12+17-3+5=x
=> x=31
7. x-(-19)-(+32)=14-(+16)
=> x+19-32=14-16
=> x=14-16+32-19
=> x=11
8. x-|-15|-|7|=-(-9)+|-5|
=> x-15-7=9+5
=> x=9+5+7+15
=> x=36
9. 15-x+17=13-(-21)
=> 15-x+17=13+21
=> -x=13+21-15-17
=> -x=2
=> x=-2
10. -|-5|-(-x)+4=3-(-25)
=> -5+x+4=3+25
=> x=3+25-4+5
=> x=29
a, \(\Leftrightarrow\)\(2x=-32\)
\(\Leftrightarrow\)\(x=-16\)
b,\(\Leftrightarrow\)\(25-\left(5x-3\right)=64\)
\(\Leftrightarrow\)\(5x-3=-39\)
\(\Leftrightarrow\)\(5x=-36\)
\(\Leftrightarrow\)\(x=-7,2\)
c,\(\Leftrightarrow\)\(25-\left(x-5\right)=15\)
\(\Leftrightarrow\)\(x-5=10\)
\(\Leftrightarrow\)\(x=15\)
\(a,\frac{3}{20}=\frac{3\times3}{20\times3}=\frac{9}{60}\)
\(\frac{7}{30}=\frac{7\times2}{30\times2}=\frac{14}{60}\)
\(\frac{4}{15}=\frac{4\times4}{15\times4}=\frac{16}{60}\)
\(c,\frac{7}{-30}=\frac{7\times4}{\left(-30\right)\times4}=\frac{28}{-120}\)
\(\frac{3}{-40}=\frac{3\times3}{\left(-40\right)\times3}=\frac{9}{-120}\)
\(-\frac{11}{30}=\frac{\left(-11\right)\times4}{30\times4}=-\frac{44}{120}\)
\(\frac{3^{15}.4+5.3^{15}}{3^{16}}=\frac{3^{15}\left(4+5\right)}{3^{16}}=\frac{3^{15}.9}{3^{16}}=\frac{3^{15}.3^2}{3^{16}}=\frac{3^{17}}{3^{16}}=3\)
\(\frac{3^{15}.4+5.3^{15}}{3^{16}}=\frac{3^{15}.\left(4+5\right)}{3^{16}}=\frac{9}{3}=3\)